Utility of the CT Scan in Diagnosing Midgut Volvulus in Patients with Chronic Abdominal Pain - Ehsan Shahverdi; Mehdi Morshedi; Maryam Allahverdi Khani; Mohammad Baradaran Jamili; Fatemeh Shafizadeh Barmi (Case Reports in Surgery)
Symptomatic intestinal malrotation first presenting in the adults is rare. Midgut volvulus is the most common complication of malrotation in the adults. Because of more differential diagnosis, Computed Tomography (CT) scan can play an important role in the evaluation of patients with this abnormality. The whirl pattern around the superior mesenteric artery found on CT scan in patients with midgut volvulus is pathognomonic and diagnostic. We describe a case of intestinal malrotation complicated by midgut volvulus in an adult patient. The preoperative CT findings were pathognomonic.